2019
DOI: 10.2478/bhk-2019-0002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with low back pain among Malaysian army personnel stationed in Klang Valley

Abstract: Study aim: The aims of this study were to examine the prevalence of low back pain (LBP) and explore possible factors associ­ated with LBP among Malaysian army personnel deployed in Klang Valley in the year 2018. Material and methods: A self-administered questionnaire on sociodemographic data, occupational background, occupational exposure and LBP evaluation was used in this study. A total of 330 respondents participated in this study and 321 (97%) of them completed and returned the questionnaires. Results: One… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Regarding occupational factors, three articles showed the association between the prevalence of LBP with lifting heavy objects ( 5 , 7 , 17 ). The prevalence of LBP is also significantly associated with working posture, such as prolonged sitting ( 7 , 18 ) and frequent standing ( 4 , 14 , 18 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding occupational factors, three articles showed the association between the prevalence of LBP with lifting heavy objects ( 5 , 7 , 17 ). The prevalence of LBP is also significantly associated with working posture, such as prolonged sitting ( 7 , 18 ) and frequent standing ( 4 , 14 , 18 ).…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of LBP is also significantly associated with working posture, such as prolonged sitting ( 7 , 18 ) and frequent standing ( 4 , 14 , 18 ). Moreover, personal lifestyle behaviours such as smoking and hobbies are reported as risk factors for LBP ( 5 , 8 , 14 ). Other risk factors of LBP included working hours and mental health ( 19 , 20 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, LBP was assessed through a questionnaire (Nordic Musculoskeletal Questionnaire) without identifying the type and region of pain. The study also included female participants (n = 27, 8%) and LBP was associated with smoking, history of LBP, history of the accident, lifting weight, and job-related activities (Chan et al, 2019). Another study conducted by Monnier et al (2015) among (n = 272) Swedish armed force marines reported 19.9% and 36.0% musculoskeletal pain originating from the thoracic and lumbar region of vertebral column, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Army occupations involve heavy physical activities, causing a higher-than-average chance of disability [3,11]. Army-related activities, such as repetitive heavy lifting, frequent twisting/bending, forceful pushing and pulling, and awkward body postures are associated with the CLBP [5,7,11,12]. Examining the occupational risk factors could prevent CLBP [5,13].…”
Section: Introductionmentioning
confidence: 99%